Structure-Function Relationships of Covalent and Non-Covalent BTK Inhibitors - Rula Zain; Rula Zain; Mauno Vihinen (Frontiers in Immunology, 2021)
Low-molecular weight chemical compounds have a longstanding history as drugs. Target specificity and binding efficiency represent major obstacles for small molecules to become clinically relevant. Protein kinases are attractive cellular targets; however, they are challenging because they present one of the largest protein families and share structural similarities. Bruton tyrosine kinase (BTK), a cytoplasmic protein tyrosine kinase, has received much attention as a promising target for the treatment of B-cell malignancies and more recently autoimmune and inflammatory diseases. Here we describe the structural properties and binding modes of small-molecule BTK inhibitors, including irreversible and reversible inhibitors. Covalently binding compounds, such as ibrutinib, acalabrutinib and zanubrutinib, are discussed along with non-covalent inhibitors fenebrutinib and RN486. The focus of this review is on structure-function relationships.